PENGINAPAN DAN MAKANAN HALAL MENJADI KUNCI MENINGKATKAN MINAT BERWISATA HALAL BAHARI DI JAKARTA - Adinda Naziha Azzahra; Sufyati HS (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Abstract Tourism is part of an important sector in a country's economy, which contributes significantly to foreign exchange earnings. Currently, halal tourism is starting to develop to meet the demands of Muslim tourists, one of which is halal marine tourism. In this study, the object of research is interest in halal maritime tourism. in Jakarta. The factors studied were accommodation, facilities, transportation, halal food and drinks. The purpose of this study is how accommodation, facilities, transportation, food and halal drinks affect the interest in halal maritime tourism in Jakarta. The research method used is a quantitative descriptive approach, data collection techniques by distributing questionnaires to tourists visiting marine tourism in Jakarta. Processing data with the SmartPLS application. The results showed that the accommodation, halal food and beverage factors had an effect on the interest in halal maritime tourism in Jakarta, while the facilities and transportation factors had no effect on the interest in halal maritime tourism in Jakarta. It is hoped that from this research the number of interests in halal maritime tourism in Jakarta will increase when accommodation, halal food and drinks have increased both in terms of quantity and quality. There needs to be a special increase in terms of facilities and transportation so that it can be a concern for tourists who want to travel halal maritime in Jakarta. Keywords: Halal Marine Tourism; Interest ;Tourism Determinan Abstrak Tujuan penelitian ini adalah bagaimana pengaruh akomodasi, fasilitas, transportasi, makanan dan minuman halal terhadap minat berwisata halal bahari di Jakarta.Metode penelitian yang digunakan adalah pendekatan deskriptif kuantitatif , teknik pengumpulan data dengan penyebaran kuesioner kepada wisatawan yang berkunjung di wisata Bahari di Jakarta.Pengolahan data dengan aplikasi SmartPLS. Hasil penelitian menunjukkan bahwa faktor akomodasi, makanan dan minuman halal berpengaruh terhadap minat berwisata halal bahari di Jakarta, sedangkan factor fasilitas dan trasportasi tidak berpengaruh terhadap minat berwisata halal Bahari di Jakarta. Diharapkan dari penelitian ini jumlah minat berwisata halal bahari di Jakarta akan meningkat ketika akomodasi, makanan dan minuman halal mengalami peningkatan baik dari segi kuantitas maupun kualitas. Perlu adanya peningkatan khusus pada segi fasilitas dan transportasi agar dapat menjadi perhatian bagi wisatawan yang ingin berwisata halal bahari di Jakarta. Kata Kunci: Faktor-Faktor Pariwisata; Minat; Pariwisata Halal bahari